Impact of Fetal Anomalies in Down Syndrome Terminations [5H]. (May 2018) - Phillips, Carolyn; Cui, Yiwen; Fanucchi, Hannah; Rijhsinghani, Asha
Abstract : INTRODUCTION: To understand the impact of an anomalous Down syndrome fetus on a woman's choice regarding her pregnancy options. METHODS: This retrospective study analyzed all women diagnosed with fetal Down syndrome by amniocentesis in the Fetal Diagnosis and Therapy Unit at The University of Iowa Hospital and Clinics between 1990 and 2006. Details of fetal findings on ultrasound examinations and subsequent decisions on pregnancy were collected. Sonographic fetal malformations were separated into structural abnormalities (limb asymmetry, facial anomalies) and major structural abnormalities (central nervous system, cardiac, gastrointestinal, genitourinary, or multiple system anomalies). RESULTS: 249 patients were included in the study of which 86 (35.5%) had no fetal anomalies on ultrasound compared to 163 (62.5%) who did. Patients without sonographic evidence of fetal structural abnormalities had a significantly higher rate of pregnancy termination than those with fetal anomalies (89.5% vs 49.1%, p<0.0001). Moreover, for patients with fetal structural abnormalities, those with non-major fetal anomalies had a statistically higher proportion of termination that those with major anomalies (80.8% vs 43.1%, p=0.0004). CONCLUSION: A woman's decision to terminate a pregnancy affected by Down syndrome may be more complex than a simple consideration of fetal anomalies, as patients in our study have higher rates of termination if they have no or non-major sonographic evidence of fetal anomalies.